Master track of ELISABETH MANN BORGESE cruise EMB360 in 1 sec resolution (zipped, 12 MB) - Helge Wolfgang Arz (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Elisabeth Mann Borgese during expedition EMB360 were processed to receive a validated master track which can be used as reference of further expedition data. During EMB360 data from the motion reference unit exail Phins Gen.3, the Trimble SPS356 GPS receiver, the Furuno GP-170 and the Furuno GP-150 GPS receiver were used to calculate the mastertrack. Data were downloaded from DAVIS SHIP data base (https://dship.bsh.de) with a resolution of 1 sec. Processing and evaluation of the data is outlined in the data processing report. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.